Efficacy and safety analysis of donafenib combined with transarterial chemoembolization in the treatment of unresectable hepatocellular carcinoma: A prospective, single-arm, single center, phase II clinical study - Chen, Hua; Song, Jinlong (Journal of clinical oncology, 2024)
e16134Background: To observe and assess the efficacy of donafenib combined with TACE in the treatment of unresectable hepatocellular carcinoma. Methods: It was a prospective, single-arm, single center, and phase II clinical study. A total of 34 initial unresectable HCC patients who had not received any systemic treatment were enrolled. The patients received donafenib ( 100mg po bid), TACE and or not and camrelizumab (200mg iv Q3W). The primary endpoint was short-term efficacy based on mRECIST criteria, with secondary endpoints including PFS, TTR, DCR and adverse events (AEs).The diameter of tumor feeding artery was measured. Results: A total of 36 patients were included in the study, including 26 who received donafenib and TACE and 10 who received donafenib and TACE plus PD-1 inhibitors. A total of 34 subjects were eligible for efficacy evaluation, and among them, there were 4 cases of CR, 17 cases of PR, 10 cases of SD and 3 cases of PD; Four patients (11.8%) successfully underwent conversion therapy and all achieved R0 resection. Two patients achieved a complete pathological response. The ORR was 61.8% and the DCR was 91.2% based on mRECIST criteria. The mPFS was 10.7 months (95%CI: 8.37-NA months), median OS was not reached, median TTR was 1.4 months ( 95% CI: 0.8-6.9 months). The 6 moths and 12 moths progression-free survival rate were 73.4% and 47.9% respectively. Treatment related adverse events (TRAEs) occurred in all 25 subjects, and grade 3 TRAE occurred in 4 subjects (11.3%), and no grade 4 or 5 TRAE occurred. The tumor feeding artery diameter was (4.5±1.4)mm pre-treatment, and reduced to (3.2±1.1)mm post-treatment (P = 0.036). The multivariable analysis indicated that the sum of baseline target lesion diameters、best tumor response and post-treatment tumor artery diameter were independent predictor for PFS. Conclusions: TACE combined with donafenib could reduce the tumor feeding artery diameter, which had a good safety profile and a high objective response rate in patients with unresectable HCC. Clinical trial information: ChiCTR2100054041.